2006
DOI: 10.1590/s1413-86702006000200012
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial function and cardiovascular diseases in HIV infected patient

Abstract: The HIV epidemic has dramatically changed the paradigm for the development of drug therapy in the last 15 years. The goal is now not only to provide an effective reduction of plasma viremia , but also to reconstitute the immune deficiency due to the progression of the disease. Significant problems with the metabolism of sugars and lipids lead to the appearance of well-documented disorders such as insulin resistance, abnormalities in lipid metabolism and lipodystrophy in those patients on prolonged therapy with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 96 publications
0
18
0
Order By: Relevance
“…The higher levels of inflammatory markers and low HDL-C levels could point to endothelial dysfunction, which is seen as the link between infection, inflammation and atherosclerosis 10. Furthermore, in the older HIV-infected participants, a positive trend of increasing peripheral cr-PWV was detected, which was not observed in the uninfected participants.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The higher levels of inflammatory markers and low HDL-C levels could point to endothelial dysfunction, which is seen as the link between infection, inflammation and atherosclerosis 10. Furthermore, in the older HIV-infected participants, a positive trend of increasing peripheral cr-PWV was detected, which was not observed in the uninfected participants.…”
Section: Discussionmentioning
confidence: 93%
“…Endothelial injury and dysfunction have been proposed as plausible links between HIV infection and atherosclerosis 9. The development of atherosclerosis may be the consequence of infection-triggered endothelial damage,10 and atherosclerotic cardiovascular events are commonly manifested via thrombotic events 11…”
Section: Introductionmentioning
confidence: 99%
“…However, serious interactions with metabolism of sugar and lipids lead to the appearance of well documented disorders such as insulin resistance, abnormalities in lipid metabolism and lipodystrophy, particularly associated with protease inhibitors (Andrade and Cotter, 2006). This leads to the decline in the use of protease inhibitors in the HAART regimen.…”
Section: Introductionmentioning
confidence: 99%
“…HAART have also been reported to significantly reduce the morbidity and mortality of HIV infection (Gea-Banacloche and Lane, 1999). Nevertheless, in the early 2000s adverse reactions began to appear and started to challenge the goals of HAART (Andrade and Cotter, 2006). Mildvan (2003) reported that many HIV positive patients receiving HAART still develop mild to moderate anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been described that in HIV + patients the incidence of premature CAD increases. It has been reported that not only the HIV infection but also the antiretroviral treatment, especially with protease inhibitors, elicits dyslipidemias 1,6,8,14 .…”
Section: Introductionmentioning
confidence: 99%